1990
DOI: 10.1093/jnci/82.4.305
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Atrial Natriuretic Factor Gene in small Cell Lung Cancer Tumors and Tumor Cell Lines

Abstract: Hyponatremia in patients with small cell lung cancer can be caused by tumor production of arginine vasopressin (AVP) and result in the syndrome of inappropriate antidiuretic hormone. In evaluating the expression of AVP mRNA from tumor and tumor cell line specimens from five patients with small cell lung cancer and hyponatremia (presumed to have the syndrome of inappropriate antidiuretic hormone), we found that the tumors and tumor cell lines from two of these five patients expressed AVP mRNA. The RNA samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Increased IL-6 in lung cancer patients enhances the acute phase response and is correlated with poor nutritional status and lowered survival (13). Both ANP and NPRA are expressed by lung cancer cells, and oversecretion of ANP has been linked with hyponatremia (14)(15)(16). However, little is known about the effects of NPRA signaling on inflammation and cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Increased IL-6 in lung cancer patients enhances the acute phase response and is correlated with poor nutritional status and lowered survival (13). Both ANP and NPRA are expressed by lung cancer cells, and oversecretion of ANP has been linked with hyponatremia (14)(15)(16). However, little is known about the effects of NPRA signaling on inflammation and cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Despite previous reports which have shown the ectopic tumor production of ANP mRNA (14,15), ANP immunoreactivity in tumor cells and supernatant (16,17), and reports of resolution of hyponatremia following surgical resection of ANP expressing tumors (16), no consistent prospective associations between elevated plasma ANP and hyponatremia have been reported in patients with lung cancer (4,15,16). Two studies of ANP in plasma and tumor cell lines showed no relationship between high levels of ANP and hyponatremia in patients with lung cancer (15,16).…”
Section: Discussionmentioning
confidence: 78%
“…However, SCLC patients with hyponatremia have been described who have no measurable AVP in their tumors (12), tumor cell lines (13), or in their plasma (10,14). Ectopic production of ANP mRNA in tumors and tumor cell lines from patients with SCLC and hyponatremia has been documented by Northern blot, S 1 -nuclease analysis, RNase protection assay, and PCR (4,14,15). ANP has been detected in SCLC tumors and tumor cell lines by RIA (14,16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Paraneoplastic hyponatremia secondary to elevated atrial natriuretic peptide (ANP) has also been reported [31] . Most SCLC cell lines have been shown to produce ANP [32,33] . Of the 23 SCLC lines examined, 16 (70%) had elevated ANP levels [33] , whereas only two (8.7%) had elevated ADH levels, and these two also had elevated ANP levels [33] .…”
Section: Hhmmentioning
confidence: 99%